Population Genetics, Evolutionary Genomics, and Genome-Wide Studies of Malaria: A View across the International Centers of Excellence for Malaria Research - Carlton, Jane M.; Volkman, Sarah K.; Uplekar, Swapna; Hupalo, Daniel N.; Alves, Joao Marcelo Pereira; Cui, Liwang; Donnelly, Martin; Roos, David S.; Harb, Omar S.; Acosta, Monica; Read, Andrew; Ribolla, Paulo E. M.; et al. (Amer Soc Trop Med & Hygiene, 2015)
The study of the three protagonists in malaria the Plasmodium parasite, the Anopheles mosquito, and the human host is key to developing methods to control and eventually eliminate the disease. Genomic technologies, including the recent development of next-generation sequencing, enable interrogation of this triangle to an unprecedented level of scrutiny, and promise exciting progress toward real-time epidemiology studies and the study of evolutionary adaptation. We discuss the use of genomics by the International Centers of Excellence for Malaria Research, a network of field sites and laboratories in malaria-endemic countries that undertake cutting-edge research, training, and technology transfer in malarious countries of the world.